TLR4 signalling: the key to controlling EV71 replication and inflammatory response - Hao, Jinfang; Wang, Hui; Lu, Xiufeng; Li, Zimo; Zhang, Xiaoyan (Frontiers in Cellular and Infection Microbiology, 2024)
Hand, foot, and mouth disease (HFMD) is a common infectious disease caused by enterovirus 71 (EV71) that frequently affects children, leading to severe infections in some cases. In general, when infection occurs, the body upregulates inflammatory responses to eliminate pathogenic microorganisms to protect the host from infection. However, EV71 may inhibit host's innate immunity to promote virus infection. At present, it is not fully understood how EV71 hijack the host cells for its own replication. Toll-like receptor 4 (TLR4), a natural immune receptor, historically associated with bacterial endotoxin-induced inflammatory responses. However, it is still unclear whether and how TLR4 is altered during EV71 infection. In this study, we observed a reduction in both TLR4 protein and gene transcript levels in RD, GES-1, and Vero cells following EV71 infection, as detected by RT-qPCR, immunofluorescence staining and western blot. Furthermore, we observed that the TLR4 downstream molecules of MYD88, p-NF-κB p65, p-TBK1 and related inflammatory cytokines were also reduced, suggesting that antiviral innate immune and inflammatory response were suppressed. To determine the impact of TLR4 changes on EV71 infection, we interfered EV71-infected RD cells with TLR4 agonist or inhibitor and the results showed that activation of TLR4 inhibited EV71 replication, while inhibition of TLR4 promote EV71 replication. Besides, EV71 replication was also promoted in TLR4 siRNA-transfected and EV71-infected RD cells. This suggests that down-regulation the expression of TLR4 by EV71 can inhibit host immune defense to promote EV71 self-replication. This novel mechanism may be a strategy for EV71 to evade host immunity.